Spin Dynamics of (Sc[Formula: see text] Lu[Formula: see text] )[Formula: see text] In Studied by Electron Spin Resonance - Cable, Archie (Appl Magn Reson, 2018)
The electron spin resonance (ESR) of conduction electrons is reported for the weak itinerant ferromagnet Sc[Formula: see text] In which, upon chemical substitution with Lu, shows a suppression of ferromagnetic correlations. A well-defined ESR lineshape of Dysonian type characterizes the spectra. The ESR linewidth, determined by the spin dynamics, displays a broad minimum only for the Sc[Formula: see text] In compound. We discuss the results using the mechanism of exchange enhancement of spin-lifetimes.